Efficacy of an interspinous decompression device versus nonoperative treatment for lumbar spinal stenosis: an example for a randomized, controlled trial. (December 2012) - Kaulhausen, Thomas; Knoell, Peter; Stein, Gregor; Siewe, Jan; Hellmich, Martin; Otto, Christina; Sayar, Annika; Yagdiran, Ayla; Beyer, Frank; Zarghonni, Kourosh; Eysel, Peer; Sobottke, Rolf
Background: Lumbar spinal stenosis (LSS) with neurogenic intermittent claudication (NIC) is one of the most common degenerative spinal diseases in the elderly. One treatment option for LSS/neurogenic intermittent claudication is conservative management with oral analgesics, injections and physical therapy. Another relatively new operative alternative is interspinous process decompression. To date, there is no convincing evidence that these devices provide any patient benefits.Methods: This study is intended as a prospective, randomized, pilot-study to compare the safety and effectiveness of a minimally invasive, percutaneously implanted interspinous process decompression device with nonoperative treatment of LSS. Patients are randomized for surgical or nonsurgical treatment. The surgical group will undergo percutaneous implantation of an interspinous device (Aperius™ PercLID, Medtronic). The control group will receive nonoperative treatment with oral nonsteroidal anti-inflammatories, injections such as epidural steroid and facet joint injections, as well as intensive physical therapy. Follow-up examinations will take place immediately after treatment during the hospital stay, after 6 weeks, and 6, 12, 24, and 36 months post-treatment. A total of 11 patients will be included in each therapy group. Outcome measurements will include objective parameters such as pain-free-walking distance and frequency of pain-medication use. The Zurich Claudication Questionnaire, a Visual Analog Scale, SF-36 scores, patients' overall status, and clinical examinations will be assessed.Summary: As new surgical techniques are developed for the treatment of LSS, it is important to evaluate the effectiveness of competing strategies. With this study, not only patient-based scores, but also objective assessments will be used to quantify patient-derived benefits of therapy.